Fostering Students’ Understanding in Mangrove Ecosystem: A Case Study Using the Mangrove Survivor Board Game - Lalipat Gitgeatpong (2022)
Background: The mangrove ecosystem is a most productive and biologically diverse ecosystem. Even though many insertional media and tools are used for educating students about the mangrove ecosystem and conservation, most media do not provide in-depth knowledge of the relationships among organisms in the mangrove ecosystem. This research created a board game as an instructional tool to help students learn about the relationship of organisms and environmental impacts on the mangrove ecosystem. Aim: The Mangrove Survivor board game was designed and developed for fostering students’ learning in the concepts relating to the relationship among organisms, biodiversity, and the impact of the key factors on living organisms to survive in the mangrove ecosystem. Method: Thirty-two students in grade 11 played the developed board game in groups of four to six. Then each group was asked to discuss and write a food web to summarize the obtained knowledge. A debriefing session was organized to confirm that all students accomplished understanding. Finally, all students were asked to complete the openended questions, questionnaire, and focus group interviews. Results: The overall results showed that students gained more knowledge and showed a positive perception toward the mangrove ecosystem. Most students also showed positive satisfaction with the developed board game which helped them to learn the concept. Conclusion: The results suggested that the mangrove Survivor board game can be a highly effective teaching and learning tool for enhancing student understanding relating to the mangrove ecosystem. Limitations of the study and suggestions for future research are discussed.